Effect of Information on Consumers’ Response to Different Food Categories Enriched With Brewer’s Spent Grain - Curutchet, Ana; Serantes, Maite; Pontet, Carolina; Prisco, Fátima; Arcia, Patricia; Barg, Gabriel; Miguez, Matías; Menéndez, Juan Andrés (Frontiers in Food Science and Technology, 2022)
Brewer’s spent grain (BSG) has been commonly considered as only a waste product, but recent research on its composition has shown that it can be a functional ingredient. The aim of this study was to analyze consumers’ attitude toward different BSG-added food products under informed conditions. BSG-enriched bread, pasta, and chocolate milk were studied exploring two major aspects. First, the eye-tracking technology was used to reveal the effect of different food labels on consumers’ attention and purchase intention. Information on sustainability and on BSG varied among the labels under analysis. The best consumers’ response occurred when the label displayed: the sustainability logo, fiber source claim, and BSG description. The phrase “Malted Barley” as an appellation of BSG was also analyzed, although it did not produce a significant effect on consumers. Second, consumers’ responses to fiber-enriched products and regular products, under informed conditions, were assayed through sensory evaluations. For bread and chocolate milk samples, no significant difference was found in acceptability between the regular and fiber-enriched versions. For pasta, on the other hand, consumers expressed a significant preference in terms of overall liking toward the fiber-enriched version. BSG-enriched products were accepted as much as the regular ones when information was provided, confirming the importance of the fiber source claim and sustainability claims.